Estimating fixed nitrogen loss and associated isotope effects using concentration and isotope measurements of NO3–, NO2–, and N2 from the Eastern Tropical South Pacific oxygen deficient zone. (October 2018) - Peters, Brian; Horak, Rachel; Devol, Alan; Fuchsman, Clara; Forbes, Matthew; Mordy, Calvin W.; Casciotti, Karen L.
Abstract: Quantifying the pathways of fixed nitrogen (N) loss in marine oxygen deficient zones (ODZs) and the isotopic fractionation caused by these processes are important for understanding the marine fixed N budget and its potential for change. In this study, a variety of approaches were used to quantify fixed N loss in the eastern tropical South Pacific Ocean (ETSP). The required measurements included nutrient concentration (nitrate—NO3 -, nitrite—NO2 -, and phosphate—PO4 3- ), gas ratio (N2 /Ar) measurements, and stable N and O isotopes in NO3 -, NO2 -, and nitrogen gas (N2 ). The dissolved inorganic nitrogen deficit calculated from [PO4 3- ] ([DIN]def, P ) exceeded the concentration of N2 gas biologically produced in the ODZ (local [N2 ]bio ) throughout the ODZ at most stations, likely due to release of PO4 3- from sediments driving up [DIN]def, P . Calculating DIN deficit using water mass analysis and local oxygen (O2 ) consumption ([DIN]def, OMP ) yielded better agreement with local [N2 ]bio than [DIN]def, P, except at the maximum [N2 ]bio, where [DIN]def, OMP misses contributions of anaerobic ammonia oxidation (anammox) to N2 production. We used the mismatch between [DIN]def, OMP and [N2 ]bio to estimate a 29% contribution of anammox to [N2 ]bio . Stable isotopic measurements of NO2 -, NO3 -, and N2 were used alongside [N2 ]bio and new estimates of [DIN]def to calculate N and O isotope effects for NO3 - reduction ( 15 εNAR and 18 εNAR, respectively), and N isotope effects for DIN removal ( 15 εDIN-R ). While the various methods for estimating [DIN]def had little effect on the isotope effects for DIN removal, differences between 15 εNAR and 15 εDIN-R, and variations with depth in the ODZ were observed. Using a simple time-dependent ODZ model, we interpreted these patterns to reflect the influences of NO2 - oxidation and NO2 - accumulation on expression of isotopic fractionation in the ODZ.